For history of scientific illustration. The case of the People’s Zoological Atlas by dr. Giovanni Boschi (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2017)
In this article, having at my disposal an original copy of People’s Zoological Atlas by dr. Giovanni Boschi, I want to comment on the epochal singularity of a culture that, at a time when it was beginning to make its own the achievements of a new scientific knowledge and the new status that followed, however, was still strongly marked by the thought, taste and even the morality of the newly passed Enlightenment period, all aimed at celebrating the centrality of humanism that characterized it. The images here exemplified reveal the great distance that separates them from what is known today as scientific image.